An Ethnographic Research of English Learning Objectives in Junior High School - Suwandi, Sahri; Baron, Rifari; Permana, Adi (Universitas Muhammadiyah Mataram, 2024)
This study aims to identify and analyze the objectives of learning English at SMP Al-Wildan International Islamic School. This study used a qualitative approach with ethnographic method. Data were collected through observations, interviews, and documentation review. Data analysis was carried out based on the model using domain analysis, taxonomy, componential and cultural theme analysis. The purpose of learning English at SMP Islam Al- Wildan International School was directed at mastering linguistic, strategic, sociocultural, actional and discourse competencies. The principles of language learning with a literacy approach involved interpretation, collaboration, convention, cultural knowledge, problem solving, reflection, and language functions. In terms of the process of learning English at SMP Islam Al-Wildan International School, the results suggest that it was very good and effective in improving the competence of mastering English because all the learning processes carried out were conducted based on careful planning